TIMING THE TUNE: THE ROLE OF REHEARSAL DURATION IN ACHIEVING QUALITY THEATRE PERFORMANCES IN THE KISII UNIVERSITY MUSIC FESTIVAL 2025 - Josephat Nehemia Nyangoga (ISI Press Institut Seni Indonesia Surakarta, 2026)
This study examines the relationship between rehearsal duration and performance quality across different music genres in the Kisii University Music Festival 2025. Guided by Deliberate Practice Theory (Ericsson, 1993), the study explores how structured and purposeful use of rehearsal time contributes to musical excellence. Specifically, it seeks to determine how much rehearsal time is sufficient to produce quality performances, whether some genres require more rehearsal time than others, and how performers and directors perceive the adequacy of rehearsal time. A qualitative research approach will be employed, using purposive sampling to select directors and performers actively involved in festival preparations and snowball sampling to identify additional key informants with relevant experience. Data will be collected through interviews, questionnaires, and performance assessments, and analyzed thematically and statistically to establish patterns linking rehearsal duration to performance outcomes. The findings are expected to provide insights into effective rehearsal time management across diverse musical genres, thereby enhancing performance planning and quality in university music festivals.